Mixed fuel strategy for carbon deposition mitigation in solid oxide fuel cells at intermediate temperatures - Su, Chao; Chen, Y.; Wang, W.; Ran, Ran; Shao, Zongping; Diniz Da Costa, J.; Liu, Shaomin (American Chemical Society, 2014)
In this study, we propose and experimentally verified that methane and formic acid mixed fuel can be employed to sustain solid oxide fuel cells (SOFCs) to deliver high power outputs at intermediate temperatures and simultaneously reduce the coke formation over the anode catalyst. In this SOFC system, methane itself was one part of the fuel, but it also played as the carrier gas to deliver the formic acid to reach the anode chamber. On the other hand, the products from the thermal decomposition of formic acid helped to reduce the carbon deposition from methane cracking. In order to clarify the reaction pathways for carbon formation and elimination occurring in the anode chamber during the SOFC operation, O2-TPO and SEM analysis were carried out together with the theoretical calculation. Electrochemical tests demonstrated that stable and high power output at an intermediate temperature range was well-maintained with a peak power density of 1061 mW cm–2 at 750 °C. With the synergic functions provided by the mixed fuel, the SOFC was running for 3 days without any sign of cell performance decay. In sharp contrast, fuelled by pure methane and tested at similar conditions, the SOFC immediately failed after running for only 30 min due to significant carbon deposition. This work opens a new way for SOFC to conquer the annoying problem of carbon deposition just by properly selecting the fuel components to realize their synergic effects.